2002
DOI: 10.1177/102831530263007
|View full text |Cite
|
Sign up to set email alerts
|

Global Education, Disempowerment, and Curricula for a World Politics

Abstract: Global education is supposed to empower. However, this article argues that global education is often premised on an idea about the inexorability of "globalization" that acts to de-politicize global life and disempower students. Though it is important to retrieve a sense of the human agency behind "globalization," this article argues that we also should work to disempower our students in certain respects, challenging their sense of interpretive privilege and cultural superiority. The article advocates trying to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…In IR curricula, if the field of knowledge reproduction is overrepresented by one particular type of scholarship, it risks being parochial. Blaney (2002) and Hovey (2004) found that the result of such curricula was that US students, having studied IR, remained largely ignorant in their knowledge of the rest of the world. The adoption of IR knowledge based on Western criteria of knowledge validity may lack relevance for Southern students and contexts; it provides inappropriate and limited analytical tools and ultimately reinforces Western intellectual dominance over the South.…”
Section: Discussionmentioning
confidence: 99%
“…In IR curricula, if the field of knowledge reproduction is overrepresented by one particular type of scholarship, it risks being parochial. Blaney (2002) and Hovey (2004) found that the result of such curricula was that US students, having studied IR, remained largely ignorant in their knowledge of the rest of the world. The adoption of IR knowledge based on Western criteria of knowledge validity may lack relevance for Southern students and contexts; it provides inappropriate and limited analytical tools and ultimately reinforces Western intellectual dominance over the South.…”
Section: Discussionmentioning
confidence: 99%
“…In a school like this, teachers are simultaneously being asked to 'empower' students through global education whilst retaining a large degree of control (over distribution and behaviour for example). It would be interesting to note here that Blaney (2002) has proposed that the ideal global education relationship in the west should actually be one of 'disempowerment' so that more affluent, western students can obtain a truer sense of global inequalities and realities. Certainly teachers talked about the delicate balance they would have to maintain for global education pedagogy to achieve its ideal form.…”
Section: Downloaded By [Northeastern University] At 07:36 27 Novembermentioning
confidence: 97%
“…When students understand their participation in a world system in terms of the interests of others, identify alternative choices, and calculate the consequences of different choices, they will engage in global thinking and rationally overhaul customary ways of valuing and acting. Instead of accepting problems prima facie, students can begin to question how they know about the world, what their role is, what it should be, and what epistemic problems limit their ability to engage in critical reflection (Blaney 2002). At work in this sort of global education is a wide variety of subdispositions in the taxonomy, including tolerance, curiosity, fortitude, individual responsibility, compassion, and responsibility for the dignity of others.…”
Section: Designing Dispositional Learningmentioning
confidence: 99%